The petrography, phase chemistry and petrology of South-West Indian Ridge basalts dredged beween 16 and 26 degrees east - Hamilton, Christopher Charles (Department of Geological Sciences, 2026)
Basaltic rocks dredged from the Southwest Indian Ridge (SWIR) between 16 and 26°E were investigated by petrographic microscope, electron microprobe and X-ray fluorescence analysis. Basalts are olivine tholeiites with geochemical characteristics similar to normal, depleted mid-ocean ridge basalts (MORB) from the SWIR between 0 and 11° East (le Roex et al., 1983). The suite consists predominantly of aphyric or microporphyritic olivine- and olivine-plagioclase basalts. Several porphyritic lavas are also present.